‘Success in Six’ model to increase efficiency and green productivity / Koh Niak Wu, Juniati Gunawan and Paulina Permatasari - Wu, Koh Niak; Gunawan, Juniati; Permatasari, Paulina (Universiti Teknologi MARA Cawangan Sarawak, 2018)
The Asian Productivity Organisation developed Green Productivity (GP) as a strategy to leverage the power of productivity in order to improve the quality of our environment. GP can foster the creative exchange between people to (i) achieve a better quality of life for all, (ii) support social justice and fairness for citizenry, and (iii) enhance prosperity for their enterprises. This study aims to demonstrate the GP “Success in Six” model on a company that has been in the bottled water industry for over 52 years and manufactures its own 3- and 5-gallon bottled water. Through the model, we perform a „walk through survey‟ method to generate and evaluate GP options with the assistance of an eco-map, i.e., a tool for mapping where the location of environmental problems and inefficiencies lie. Subsequently, we leverage on Material Flow Cost Accounting (MFCA) as a quantitative tool to provide recommendations that increase their resource productivity and reduce operational costs. From the analysis and through a material flow profit-and-loss statement, we observe that the proportion of positive products to negative products was 77% to 23%. The GP recommendation resulted in a 55% raw material cost reduction and 10% increase in recycling earnings.